Peningkatan Hasil Belajar Lompat Tinggi Melalui Modifikasi Permainan Sebut Nama (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of the research is to increase the study result of high jump for the 4th-grade class student of Setu 02 elementary school in Tarub district Tegal regency in the academic year 2013/2014. This research method is Classroom Action Research (CAR), which carried out the research subjects are students the 4th-grade class student of Setu 02 elementary school, amounting to 23 students consisting of 12 boys and 11 girls. Data analysis using quantitative and qualitative data analysis. The results of the second cycle of research, an increase in study’s result of 22% of the first cycle, it is 96% the details of 22 students successfully pass the study and there is only one student is still not finished with the grounds trauma to the high jump. From the results of this research with CAR method can be concluded that the high jump learning using game say a name successfully to increase the ability of high jump.